INTERRELATIONSHIP BETWEEN METABOLIC RISK FACTORS IN ELDERLY PATIENTS WITH ISCHEMIC HEART DISEASE AND ARTERIAL HYPERTENSION - Kholmatov Sh.A; Tulaboeva G.M; Tolipova Yu.Sh; Sagatova Kh.M; Kamolov B.B; Kurbonov N.B. (Western European Studies, 2025)
This study analyzed the interrelationship between metabolic risk factors in elderly patients with comorbid conditions such as ischemic heart disease (IHD) and arterial hypertension (AH). Two groups were compared in terms of blood glucose, lipid profile, inflammatory marker (Creactive protein), nitrogenous metabolites (urea, creatinine), and glomerular filtration rate (GFR). The results showed that in patients with both IHD and AH, there were strong correlations between metabolic indicators, with inflammatory and nephrofunctional changes appearing earlier. This indicates the need for comprehensive and early monitoring in this group to prevent cardiovascular complications.
Keywords: metabolic risk factors; ischemic heart disease; arterial hypertension